Implementation of Science Module Based on Microcontroller to Improve Students’ Computational Thinking Skills in Earth Science Course - Mustofa Mustofa; Joko Waluyo; Yushardi Yushardi; Zainur Rasyid Ridlo (Jurnal Penelitian Pendidikan IPA, 2025)
The aim of this research is to explore the computational thinking skills using Microcontroller under implementation of science module. Computational thinking is not only an investment in computer science, but can be applied across disciplines as a step towards solving higher-order thinking problems. Improving computational thinking skills helps students to adapt to the digital age of the 21st century. To improve these skills, a tool or media is needed, such as a learning module, that can guide students in performing activities in this area. This module contains student activity using microcontrollers as a tool for collecting data. The analysis data include practicality and effectiveness of the science module. The method used was a group pre-post test as learning assessment and use practicality observation sheet, student pretest - posttest and student response questionnaire. The results of this study are the practicality of 92% which is declared very practical, and the effectiveness of 0.78 obtained from the n-gain analysis which means it is quite effective, the p-value of paired sample t-test is less than the threshold of 0.05 which indicates a significant increase in students' computational thinking skills and direct student experience in connecting sensors related to technological applications applied in the world of agriculture and get a positive response with a score of 72% with a good category. From the results of the analysis obtained, it can be concluded that the implementation of the module can improve students' computational thinking skills